Contact dermatitis to hair cosmetics: Current diagnostic recommendations. (24th August 2021) - Thomas, Zita‐Rose Manjaly; Jamiolkowski, Dagmar; Chantraine, Sibylla; Steveling‐Klein, Esther; Hofmeier, Kathrin Scherer; Hartmann, Karin
Summary: Hair cosmetics such as shampoos, hair dyes, bleaching agents or hair straightening creams contain frequent contact allergens. These can lead to allergic contact dermatitis especially in hairdressers, but also in their customers and in others who use hair products at home. While hairdressers suffer mainly from hand dermatitis, in customers and home‐users, dermatitis primarily affects the head, neck and face. In this mini‐review, we propose a diagnostic algorithm in two steps, based on patch testing, that can be used for the assessment of suspected hair product‐induced contact dermatitis. In a first step, we recommend testing the German Contact Allergy Group (DKG) standard series, DKG ointment series, DKG preservative series, DKG hairdresser series, DKG fragrance series as well as (especially in hairdressers) the DKG rubber series. In a second step, if the culprit allergen cannot be identified with the help of the standardized test series and there is a well‐founded suspicion, testing the patient's own products, such as shampoos, hair sprays and hair dyes, is recommended.